Sheng-Jiang powder ameliorates NAFLD via regulating intestinal microbiota in mice - Zhang, Pengcheng; Li, Juan; Miao, Yifan; Zhao, Xianlin; Zhu, Lv; Yao, Jiaqi; Wan, Meihua; Tang, Wenfu (Frontiers in Microbiology, 2024)
Background: Intestinal microbiota have been demonstrated to be involved in the development of NAFLD, while the relationship between the severity of NAFLD and intestinal microbiota is still not fully elucidated. Sheng-Jiang Powder (SJP) showed exact efficacy in treating SFL and great potential in regulating intestinal microbiota, but the effects need to be further addressed in NASH and liver fibrosis. Objectives: To investigate the differences in intestinal microbiota of NAFLD with different severity and the effect of SJP on liver damage and intestinal microbiota. Design: NAFLD mice models with different severity were induced by high-fat diet (HFD) or choline-deficient, L-amino acid-defined high-fat diet (CDAHFD) feeding and then treated with SJP/normal saline. Methods: Biochemical blood tests, H&E/Masson/Oil Red O/IHC staining, Western blot, and 16SrDNA sequencing were performed to explore intestinal microbiota alteration in different NAFLD models and the effect of SJP on liver damage and intestinal microbiota. Results: Intestinal microbiota alteration was detected in all NAFLD mice. SJP induced increased expression of Pparγ and alleviated liver lipid deposition in all NAFLD mice. Microbiome analysis revealed obvious changes in intestinal microbiota composition, while SJP significantly elevated the relative abundance of Roseburia and Akkermansia, which were demonstrated to be beneficial for improving inflammation and intestinal barrier function. Conclusion: Our results demonstrated that SJP was effective in improving lipid metabolism in NAFLD mice, especially in mice with SFL. The potential mechanism may be associated with the regulation of intestinal microbiota.